A new species of Typhlodromus Scheuten (Acari: Phytoseiidae) from Brazil - Lofego, Antonio C.; Feres, Reinaldo J. F. [UNESP] (My University, 2006)
A new species of phytoseiid mites is described from Brazil, Typhlodromus moraesi sp. nov., collected on Tabebuia alba (Cham.) Sandwith and Chamaesyce hirta (L.) Millsp. in the State of São Paulo. This is the second species of the T. arizonicus group. Copyright © 2006 Magnolia Press.
Keywords: Phytoseiidae; Typhlodromus arizonicus group; Typhlodromus moraesi sp. nov.; Acari; Chamaesyce hirta; Tabebuia; Typhlodromus